The visualization of cattle movement data in the state of Pará in 2016 through networks of animal transit graphs and guides - De Aragão, Samuel Carvalho; Pontes, Agnaldo Reis; Gouveia, Luis Manuel Borges; Lopes, Samuel Franco; Katsuda, Pier Kenji Rauschkolb [UNESP]; Pereira, Anirene Galvão Tavares [UNESP]; Oliveira, Márcio Teixeira; De Oliveira, Jefferson Pinto; Do Socorro Brito Coroa, Rita; Araújo, Gilson Ferreira; De Siqueira, Marcio Merêncio Panza (My University, 2018)
Animal movement is inherent in the marketing between the rural productive units, establishing space-time connections between them. The relational nature of such information is kept in the Animal Transit Guides (GTA), a mandatory issuance in Brazil. When evaluating such set of information, this work aimed at characterizing the bovine movement network in the state of Pará through the application of concepts from Social Network and Network Theory analysis. Where the nodes and edges that structure the network are respectively the rural properties and the number of cattle moved between them. The results obtained characterize the bovine movement in the state, which show distinct patterns such as the movement of a great number of animals rambling and a clear seasonality due to commercialization purposes. The evaluation of the network components’ modularity also shows the subdivision of the state in four commercial clusters, where the central measures of its components define municipalities of economic and epidemiological interest. The results described herein help in the support of health surveillance and control measures, as well as the adoption of economic strategies and policies.
Keywords: Commercial agglomerates; Network theory; SNA; Veterinary epidemiology